Motivation in the classroom - López Muñoz, Luis (Pulso. Revista de educación, 2004)
Motivation in the classroom has its bases, its meaning, and its strategies. The natural drive of children to learn may not be apparent within the structured and regulated educational system they are placed in. We aim to highlight the profound connection between the student’s personal history, the interpersonal educational relationship that emerges, and the classroom activities such as daily routines and tasks that take place in the physical environment where learning occurs.